Lung function trajectories in children with early diagnosis of non-cystic fibrosis bronchiectasis: a retrospective observational study - Rossella Lamberti; Simona Ferraro; Andrea Farolfi; Michele Ghezzi; Salvatore Zirpoli; Alice Marianna Munari; Sai Spandana Adivishnu; Giuseppe Marano; Elia Biganzoli; Gian Vincenzo Zuccotti; Enza D’Auria (Italian Journal of Pediatrics)
Abstract Background Non-cystic fibrosis (non-CF) bronchiectasis (BE) is defined as a clinical syndrome of recurrent, persistent wet cough and abnormal bronchial dilatation on chest High Resolution Computed Tomography (HRCT) scans. The aims of this study were to characterize the pattern of the trajectories of lung function parameters and to consider the relationship between the lung function and radiological severity according to the modified Reiff score. Methods The study retrospectively considered 86 children (46.5% male, median age of 4 years) with non-CF BE, admitted at the Paediatric Pneumology Unit of Buzzi Children’s Hospital from January 2015 to December 2022. The diagnosis of BE was made according to the presence of a suggestive clinical history and symptoms and key features of BE evidenced on chest HRCT scans. The modified Reiff score was adapted to quantify the severity of BE. Spirometry (COSMED MicroQuark spirometer) was performed at median age of 5.78 years (baseline or T0) and after 1 and 2 years from the baseline (T1 and T2, respectively). The general trends of lung function parameters were estimated by ANOVA models for repeated measurements. For each lung function parameter, a longitudinal regression model was fitted. The analysis was performed with the software R release 4.2.3. The statistical significance was deemed when the p-value resulted lower than 0.05. Results The general trends of lung function parameters showed a statistically significant variation of forced vital capacity (FVC%) and forced expiratory volume in 1s (FEV1%) from T0 to T1 (p = 0.0062, 0.0009) and no significant change for FVC%, FEV1% and forced expiratory flow 25–75% of VC (FEF25/75%) from T1 to T2 (p = 0.145, 0.210, 0.600, respectively). Notably, we found no correlation between the age at diagnosis and the lung function parameters at T0 (r = 0.149, 0.103 and 0.042 for FVC%, FEV1% and FEF25/75%, respectively). Instead, a poor negative correlation resulted between the Reiff score and FVC%, FEV1% e FEF25/75% at baseline (Spearman coefficients: rho=-0.156, -0.204, -0.103, respectively). Conclusions A stable pulmonary function is detectable within 2 years follow up from baseline spirometry. The modified Reiff score should be considered as a good tool not only to quantify the radiological lung involvement but also the degree of pulmonary function impairment.